Paper Airplane Toys: Interpreting Children’s Thinking - Irfan Fauzi; Jiraporn Chano; Mia Komariah; Salma Ihsani Fhilrizki; Herli Salim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The article aimed to analyze the students' critical thinking and problem-solving skills in making paper airplane toys. It is phenomenology research that was conducted on elementary school students with a total of 15 students. The data collection techniques used documentation and interviews. Because of the form of the data obtained descriptive, the analysis was carried out qualitatively, namely by coding with the flow of data reduction, data presentation, and conclusion. The results showed that the students apply critical thinking and problem-solving concepts in making paper airplane toys. Several other factors were students planning and designing carefully, measuring in detail with mathematical concepts and estimating what allows paper airplanes to fly for a long time or even for a short time. This research contributed to creating learning that develops critical thinking skills and problem-solving through simple things close to children's lives (contextual). Keywords: STEM, Critical Thinking, Paper Airplane Toys